2021
DOI: 10.3390/ijms222111972
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Combinatorial Pharmacological Treatments to Correct Nonsense Mutations in the CFTR Gene

Abstract: Cystic fibrosis (CF) is caused by loss of function of the CFTR chloride channel. A substantial number of CF patients carry nonsense mutations in the CFTR gene. These patients cannot directly benefit from pharmacological correctors and potentiators that have been developed for other types of CFTR mutations. We evaluated the efficacy of combinations of drugs targeting at various levels the effects of nonsense mutations: SMG1i to protect CFTR mRNA from nonsense-mediated decay (NMD), G418 and ELX-02 for readthroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
(107 reference statements)
4
16
1
Order By: Relevance
“…Several strategies have been proposed in pre-clinical models to prevent NMD and enhance mRNA expression of PTC CFTR (reviewed in [ 266 , 267 ]). Inhibition of the NMD activator serine/threonine-protein kinase SMG1, via the small molecule inhibitor SMG1i, resulted in increased levels of G542X, W1282X and other PTC containing mRNAs in various models, including airway epithelial cells, primary rectal organoids and several CF animal models [ 58 , 268 , 269 , 270 , 271 , 272 , 273 , 274 ]. As SMG1 is active in other cellular processes besides NMD, its inhibition causes considerable toxicity, which likely precludes it from translation into a therapy [ 272 , 275 ].…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been proposed in pre-clinical models to prevent NMD and enhance mRNA expression of PTC CFTR (reviewed in [ 266 , 267 ]). Inhibition of the NMD activator serine/threonine-protein kinase SMG1, via the small molecule inhibitor SMG1i, resulted in increased levels of G542X, W1282X and other PTC containing mRNAs in various models, including airway epithelial cells, primary rectal organoids and several CF animal models [ 58 , 268 , 269 , 270 , 271 , 272 , 273 , 274 ]. As SMG1 is active in other cellular processes besides NMD, its inhibition causes considerable toxicity, which likely precludes it from translation into a therapy [ 272 , 275 ].…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…In contrast to PTC124, ELX-02 has been shown to restore CFTR function in G542X human rectal organoids [ 309 ]. Moreover, it was able to rescue several other PTC mutations in isogenic human bronchial cell lines (16HBEge) [ 268 ]. Here, ELX-02 was combined with several other treatments, including NMD suppressors, amplifiers, correctors and potentiators, to reach maximum functional rescue.…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional rescue observed corresponded to about 30% of wt-CFTR and it will likely translate into clinical benefit. Considering that the two only individuals described with this mutation are compound heterozygous for W1282X, it is even more likely that they will get benefit VX-661 + VX-445 + VX-770 because, although being a nonsense mutation, its location closer to the C-terminus of CFTR and may allow the existence of some truncated and functional protein [ 39 ]. However, the rescue observed for H1079P-CFTR was lower than that in cells expressing F508del-CFTR for the same drug combination, for which correction brings it to almost wt-CFTR levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent in vitro investigations by Galietta and co-workers showed that 8 , as expected, was effective in improving the rescue of F508del-CFTR but failed to increase the rescue of other CFTR mutants, such as G542X-CFTR or W1282X-CFTR, in combination with read-through agents and/or nonsense-mediated mRNA decay (NMD) inhibitors. 65 Further experiments on HBE cells showed that 8 could also significantly enhance ENaC and TMEM16A channels’ activities. Such results suggest that CFTR amplifiers may alter the expression and/or function of other proteins involved in transepithelial ion transport, 65 calling for the need for further investigations.…”
Section: Targeting Rna Binding Proteinsmentioning
confidence: 97%